Effects of Ethanolic Extract and Naphthoquinones Obtained from the Bulbs of Cipura paludosa on Short‐Term and Long‐Term Memory: Involvement of Adenosine A1 and A2A Receptors. (31st December 2012) - Lucena, Greice M. R. S.; Matheus, Filipe C.; Ferreira, Vania M.; Tessele, Priscila B.; Azevedo, Mariangela S.; Cechinel‐Filho, Valdir; Prediger, Rui D.
Abstract Previous studies from our group have indicated important biological properties of the ethanolic extract and isolated compounds from the bulbs of Cipura paludosa (Iridaceae), a native plant widely distributed in northern Brazil, including antioxidant, neuroprotective and anti‐nociceptive activities. In the present study, the effects of the ethanolic extract and its two naphthoquinones (eleutherine and isoeleutherine) on the short‐ and long‐term memory of adult rodents were assessed in social recognition and inhibitory avoidance tasks. Acute pre‐training oral administration of the ethanolic extract improved the short‐term social memory in rats as well as facilitated the step‐down inhibitory avoidance short‐ and long‐term memory in mice. Moreover, the co‐administration of 'non‐effective' doses of the extract of Cipura paludosa and the adenosine receptor antagonists caffeine (non‐selective), DPCPX (adenosine A1 receptor antagonist) and ZM241385 (adenosine A2A receptor antagonist) improved the social recognition memory of rats. In the inhibitory avoidance task, the co‐administration of sub‐effective doses of the extract with caffeine or ZM241385, but not with DPCPX, improved the short‐ and long‐term memory of mice. Finally, the acute oral administration of eleutherine and isoeleutherine facilitated the inhibitory avoidance short‐ and long‐term memory in mice. These results demonstrate for the first time the cognitive‐enhancing properties of the extract and isolated compounds from the bulbs of Cipura paludosa in rodents and suggest a possible involvement of adenosine A1 and A2A receptors in these effects.